DAMPAK PENGALIHAN PBB-P2 MENJADI PAJAK DAERAH PELUANG DAN TANTANGAN - Munawaroh, Siti; Nuryantika, Roliah; Rahayu, Santy; Sari, Shanty Puspita; Rustiyaningsih, Sri (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2014)
Minister of Finance and Minister of Domestic Affairs to establish rules jointly the regulation from Minister of Finance no.213/PMK.07/2010 and regulation from Minister of Domestic Affairs no. 58 of 2010 on the preparation stage of the transfer of Land and Building TaxÂ  the Region and Urban areas where taxes are included in Law no. 28 of 2009 on Local Taxes and Charges (LTC) to be validÂ  on 15 September 2009, apply from 01 January 2010 as subtitute of Law no. 34 of 2000 about LTC as the legal basic to formulate a PBB-P2 transfer to local taxes. Local taxes are the main source of local own revenue that must be managed optimally so that the construction goes smoothly. This article aims to determine the impact of PBB-P2 transfer to the local tax opportunities and challenges for local governments. With the impact that, the tax payers are expected to understand and to obey regulations that have been there and can feel the service of PBB-P2.